Similar cost of Hamiltonella defensa in experimental and natural aphid‐endosymbiont associations. Issue 1 (24th January 2022) - Kaech, Heidi; Jud, Stephanie; Vorburger, Christoph
Abstract: Endosymbiont‐conferred resistance to parasitoids is common in aphids, but comes at a cost to the host in the absence of parasitoids. In black bean aphids ( Aphis fabae ), costs in terms of reduced lifespan and lifetime reproduction were demonstrated by introducing 11 isolates of the protective symbiont Hamiltonella defensa into previously uninfected aphid clones. Transfection of H .  defensa isolates into a common genetic background allows to compare the costs of different endosymbiont isolates unconfounded by host genetic variation, but has been suggested to overestimate the realized costs of the endosymbiont in natural populations, because transfection creates new and potentially maladapted host–symbiont combinations that would be eliminated by natural selection in the field. In this experiment, we show that removing H .  defensa isolates from their natural host clones with antibiotics results in a fitness gain that is comparable to the fitness loss from their introduction into two new clones. This suggests that estimating cost by transfecting endosymbiont isolates into a shared host genotype does not lead to gross overestimates of their realized costs, at least not in the two recipient genotypes used here. By comparing our data with data reported in previous publications using the same lines, we show that symbiont‐induced costs may fluctuate over time. Thus, costs estimated after extended culture in the laboratory may not always be representative of the costs at the time of collection in the field. Finally, we report the accidental observation that two isolates from a distinct haplotype of H .  defensa could not be removed by cefotaxime treatment, while all isolates from two other haplotypes were readily eliminated, which is suggestive of variation in susceptibility to this antibiotic in H .  defensa . Abstract : In this experiment, we show that removing isolates of the bacterial endosymbiont Hamiltonella   defensa from their natural aphid host clones with antibiotics results in a fitness gain that is comparable to the fitness loss from their introduction into new clones. This suggests that estimating costs by transfecting endosymbiont isolates into a shared host genotype does not lead to gross overestimates of their realised costs.